Community based Epidemiological study of injury in India. (7th October 2012) - Verma, Pramod Kumar
Abstract : Background: WHO, SEARO sponsored this study to find various epidemiological factors of injury before planning preventive strategies. Objective: To find various epidemiological factors of injury. Methods: This is a retrospective 1-year descriptive epidemiological study of various types of injuries among 30 554 population of Delhi. Results: 2232 injuries were observed with Annual incidence Rate (IR) 73.1/1000 population. The injuries were more among under 5 years of age ( IR 90.7) followed by age group of 5–25 years (48%), 25–45 age group (28%). Males had double incidence (IR94.9) as compared to females (IR47.6). Incidence of injury was more among lower educated group (primary education IR79.6), as compared to educated (postgraduate group IR66.1). Business group most affected (IR95) followed by labour class IR(92.9) and least among housewives (IR52.1). Limbs (IR37.4 lower limbs and IR27.3 upper limbs) were most often injured. Head injuries were more common among fall (179 followed by mechanical injury (36) and homicidal injuries (14). Superficial injuries were most common (IR 51.3) followed by fracture (14.1%) and concealed injuries (13.6%). In case of traffic injuries, crush injuries (96 cases) were more common. Fall (832 cases) was most common followed by traffic injury (680 cases). Both injuries account for 69% of total cases. 69% injuries occurred during routine work, 20.47% during recreation activities, 3.9% due to hurry and 2.4% due to fatigue after work. Significance: Based on the epidemiology of injury, specific risk population/risk factors can be identified and accordingly preventive measures can be planned for community.